MODEL PREDIKSI FINANCIAL DISTRESS (Studi pada perusahaan Manufaktur Sektor Konsumsi yang Terdaftar di Bursa Efek Indonesia) - Cahya, Arif Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This study aims to determine the existence of a state of financial difficulties for companies that could potentially experience financial distress in the consumption sector manufacturing companies using models Springate (S-Score), Model Zmijewski (X-Score, and Model Grover (G-Score). This type of research is included in descriptive research that describes the current condition of the company with the type of quantitative data. The population in this study is the consumption sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2018, totaling 5 companies. The sample selection was carried out using the saturated sample method. The results showed that PT. Bumi Teknokultura Unggul Tbk has the potential to experience bankruptcy from the results of 3 financial distress calculation models. PT Budi Stratch & Sweetener Tbk also experienced potential bankruptcy in the Springate model. The remaining PT Akasha Wira International Tbk and PT Nippon Indosari Corporindo Tbk also show the potential bankruptcy of the models Springate year 2017.Â Keywords: Financial Distress, Model Springate , Model Zmijewski , Model Grover .Â